ТЕНДЕНЦИИ И ИНТЕГРАЦИЯ ИННОВАЦИОННОЙ ДЕЯТЕЛЬНОСТИ КАК ОСНОВА ПОВЫШЕНИЯ КАЧЕСТВА ОБРАЗОВАНИЯ (из опыта работы кафедры русского языка и литературы) - Ходжаниязова, А.А.; Генжебаева, Г.К. (SCIENCE and SOCIETY, 2022)
The article is devoted to the current problem of the trends and integrations of innovative activities in the system of higher education. The stages are being updated for development of innovative activity in Uzbekistan. The characteristic features of the practical application of innovation integration are singled out and described. The practical experience of applying the trend and innovative activities is summarized as a basis for improving the quality of education.
Keywords: trends; innovations; reform; higher education; efficiency improvement; international partnership